Podocyte injury underlies the progression of focal segmental glomerulosclerosis in the fa/fa Zucker rat - Gaßler, Nikolaus; Elger, Marlies; Kränzlin, Bettina; Kriz, Wilhelm; Gretz, Norbert; Hähnel, Brunhilde; Hosser, Hiltraud; Hartmann, Ingrid (Kidney international, 2001)
Podocyte injury underlies the progression of focal segmental glomerulosclerosis in the fa/faZucker rat. - Background - The progression of diabetic nephropathy to chronic renal failure is based on the progressive loss of viable nephrons. The manner in which nephrons degenerate in diabetic nephropathy and whether the injury could be transferred from nephron to nephron are insufficiently understood. We studied nephron degeneration in the fa/fa Zucker rat, which is considered to be a model for non-insulin-dependent diabetes mellitus. - Methods - Kidneys of fa/fa rats with an established decline of renal function and of fa/+ controls were structurally analyzed by advanced morphological techniques, including serial sectioning, high-resolution light microscopy, transmission electron microscopy, cytochemistry, and immunohistochemistry. In addition, tracer studies with ferritin were performed. - Results - The degenerative process started in the glomerulus with damage to podocytes, including foot process effacement, pseudocyst formation, and cytoplasmic accumulation of lysosomal granules and lipid droplets. The degeneration of the nephron followed the tuft adhesion-mediated pathway with misdirected filtration from capillaries included in the adhesion toward the interstitium. This was followed by the formation of paraglomerular spaces that extended around the entire glomerulus, as well as via the glomerulotubular junction, to the corresponding tubulointerstitium. This mechanism appeared to play a major role in the progression of the segmental glomerular injury to global sclerosis as well as to the degeneration of the corresponding tubule. - Conclusions - The way a nephron undergoes degeneration in this process assures that the destructive effects remain confined to the initially affected nephron. No evidence for a transfer of the disease from nephron to nephron at the level of the tubulointerstitium was found. Thus, each nephron entering this pathway to degeneration appears to start separately with the same initial injuries at the glomerulus.